The influence of indicators of socio-cultural adaptation, social support and coping strategies on the mental health of Chinese students - Tao, Su; Fourmanov, Igor A. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
It was found that the mental health scores of Chinese students have a significant inverse relationship with the level of socio-cultural adaptation, indicators of active coping and social support, as well as a direct link with passive coping. Socio-cultural adaptation and social support do not directly affect mental health indicators. Active coping negatively affects mental health indicators (reduces the risk of disorders), and passive coping, on the contrary, catalyses mental health problems. Social support has a significant moderating effect on the mediation of active and passive coping in the regulation of mental health. The conducted research allowed us to draw an important scientific and practical conclusion that the problems of the mental state and health of Chinese students can be overcome by teach them how to actively overcome stressful situations in the process of socio-cultural adaptation, as well as expanding the quality and quantity of social support.
Keywords: socio-cultural adaptation; active and passive coping; social support; mental health